The Misconceptions in science among students of the Faculty of Science at Palestine Technical University Kadoorie - Iter, Nuha Ismail (Journal of Educational and Psychological Sciences, 2023)
This study aimed to detect misconceptions in science among students of the Faculty of Science at Palestine Technical University Kadoorie, and interpretation reasons for the existence of misconceptions among students, and to identify piloted strategies and teaching models that can modify and change the misconceptions. The study used a conceptual test to assess the student understanding of science concepts. The test consisted of (50) multiple-choice items for basic science concepts in chemistry, physics and life sciences. The test was applied to a sample of (52) students from the Faculty of Science at Palestine Technical University Kadoorie. The study concluded that: The percentages of the students’ average answers to the test indicate the presence of misconceptions among students from College of Science in the three fields are: in life sciences (64.93%) and ranged between (28.85%-94.23%), in chemistry (63.46%), and it ranged between (44.23%- 96.15%), and in physics (61.73%), and it ranged between (34.62%- 88.46%). The high rates of misconceptions items, correspondingly: In chemistry “the anode charge in electrolysis cells is positive” with (96.15%), but, the correct answer is that the anode charge in electrolysis cells is negative. In life sciences, “the respiration is defined as a process: the exchange of gases between blood and cells, or inhalation and exhalation” with (94.23%). In physics “the magnitude inside the elevator move with gravitational acceleration is different from the weight of the real person with (88.46%), and the fact is that the weight of the person inside the elevator is equal to the real weight of the person. From the disk review there are teaching strategies that are piloted and have a significant value in changing the misconception such as: Van Haile’s theory, games and role-playing, initiative organizations, DEN & DEN model, Posner’s model through the computer, Karen’s model. In light of these findings, the in light of results the study recommended that: there are a need to hold discussion sessions with members of the teaching staff in the Faculty of Science in order to discuss these misconceptions with them, and to push them apply verified strategies to change these misconceptions.